Aggressive intravenous hydration with lactated Ringer’s solution for prevention of post-ERCP pancreatitis: a prospective randomized multicenter clinical trial - Park, Chang-Hwan; Paik, Woo Hyun; Park, Eun Taek; Shim, Chan Sup; Lee, Tae Yoon; Kang, Changdon; Noh, Myung Hwan; Yi, Sun Youn; Lee, Jong Kyun; Hyun, Jong Jin; Lee, Jun Kyu (Endoscopy, 2018)
Background and study aims The present study aimed to determine the type of intravenous hydration that is best suited to reducing the incidence of post-endoscopic retrograde cholangiopancreatography (ERCP) pancreatitis.Patients and methods In a prospective randomized multicenter trial, average-to-high risk patients who underwent first-time ERCP were randomly assigned to three groups (1:1:1) who received: aggressive intravenous hydration (3 mL/kg/h during ERCP, a 20-mL/kg bolus and 3 mL/kg/h for 8 hours after ERCP) with either lactated Ringer’s solution (LRS) or normal saline solution (NSS), or standard intravenous hydration with LRS (1.5 mL/kg/h during and for 8 hours after ERCP). The primary end point was post-ERCP pancreatitis (PEP).Results 395 patients were enrolled, and 385 completed the protocols. The three groups showed no significant differences in demographic characteristics. There was a significant difference in the intention-to-treat (ITT) PEP rate between the aggressive LRS group (3.0 %, 95 % confidence interval [CI] 0.1 % – 5.9 %; 4 /132), the aggressive NSS group (6.7 %, 95 %CI 2.5 % – 10.9 %; 9 /134) and the standard LRS group (11.6 %, 95 %CI 6.1 % – 17.2 %; 15 /129; P = 0.03). In the two-group comparisons, the ITT PEP rate was significantly lower for the aggressive LRS group than for the standard LRS group (relative risk [RR] 0.26, 95 %CI 0.08 – 0.76; P = 0.008). There was no significant difference in the ITT PEP rate between the aggressive NSS group and the standard LRS group (RR 0.57, 95 %CI 0.26 – 1.27; P = 0.17).Conclusion Aggressive hydration with LRS is the best approach to intravenous hydration for the prevention of PEP in average-to-high risk patients.